THE EFFECT OF CHATGPT USAGE INTENSITY ON STUDENTS' LEARNING EFFECTIVENESS AT TANGERANG RAYA UNIVERSITY - Rahma Miftahul Jannah; Ahmad Rifai; Intan Oktaviani; Devika Nur Fadlin; Dewi Purwati; Sonya Trikandi; Febri Sari Siahaan (Journal of Social and Economics Research, 2026)
The development of artificial intelligence (AI) technology has drastically transformed the world of education, particularly at the university level. One popular AI application among students is ChatGPT. ChatGPT's ability to present information quickly, facilitate understanding of material, and support assignment completion has made it a widely used learning tool. This study aims to investigate the impact of ChatGPT usage frequency on student learning effectiveness at the University of Tangerang Raya. The methodology used was quantitative through a survey. Data collection was conducted by distributing questionnaires to active students who had utilized ChatGPT in their studies. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) method. The results of this study indicate that the frequency with which students use ChatGPT has a significant positive impact on their learning effectiveness. Students who regularly use ChatGPT tend to have a deeper understanding of the course material, increase learning efficiency, and perform better at completing assignments. These findings suggest that appropriate use of ChatGPT can serve as an educational tool that improves the quality of students' learning experiences.